NOP receptor antagonists decrease alcohol drinking in the dark in C57BL/6J mice - Brunori, Gloria (Alcohol Clin Exp Res, 2019)
BACKGROUND: The nociceptin/orphanin FQ opioid peptide (NOP) receptor and its endogenous ligand N/OFQ have been implicated in the regulation of drug and alcohol use disorders. In particular, evidence demonstrated that NOP receptor activation blocks reinforcing and motivating effects of alcohol across a range of behavioral measures, including alcohol intake, conditioned place preference and vulnerability to relapse. METHODS: Here, we show the effects of pharmacological activation and inhibition of NOP receptors on binge-like alcohol consumption, as measured by the “drinking in the dark” (DID) model in C57BL/6J mice. RESULTS: We found that two potent and selective NOP agonists AT-202 (0, 0.3, 1, 3 mg/kg) and AT-312 (0, 0.3, 1 mg/kg) did not affect binge alcohol drinking at doses that do not affect locomotor activity. AT-202 also failed to alter DID behavior when administered to mice previously exposed to chronic alcohol treatment with an alcohol-containing liquid diet. Conversely, treatment with either the high affinity NOP receptor antagonist SB-612111 (0, 3, 10, 30 mg/kg) or the selective antagonist LY2817412 (0, 3, 10, 30 mg/kg) decreased binge drinking. SB-612111 was effective at all doses examined, LY2817412 was effective at 30 mg/kg. Consistently, NOP receptor knockout mice consumed less alcohol compared to wild type. SB-612111 reduced DID and increased sucrose consumption at doses that do not appear to affect locomotor activity. However, the high dose of SB-612111 (30 mg/kg) reduced alcohol intake but failed to inhibit preference in a two-bottle choice DID model that can assess moderate alcohol intake. CONCLUSIONS: The present results suggest that NOP receptor inhibition rather than activation may represent a valuable approach for treatment of alcohol use disorders characterized by excessive alcohol consumption such as binge drinking.